Tyrosol Facilitates Neovascularization by Enhancing Skeletal Muscle Cells Viability and Paracrine Function in Diabetic Hindlimb Ischemia Mice - Zhang, Jianqi; Nugrahaningrum, Dyah Ari; Marcelina, Olivia; Ariyanti, Agnes Dwi; Wang, Guixue; Liu, Caiping; Wu, Shourong; Kasim, Vivi (Frontiers in Pharmacology, 2019)
As one of the most severe manifestations of diabetes, vascular complications are the main causes of diabetes-related morbidity and mortality. Hyperglycemia induces systemic abnormalities, including impaired angiogenesis, causing diabetic patients to be highly susceptible in suffering hind-limb ischemia (HLI). Despite its severe prognosis, there is currently no effective treatment for diabetic HLI. Skeletal muscle cells secrete multiple angiogenic factors, hence recently are reported to be critical for angiogenesis; however, hyperglycemia disrupted the paracrine function in skeletal muscle cells, leading to the impaired angiogenesis potential observed in diabetic patients. The present study showed that tyrosol, a phenylethanoid compound, suppresses accumulation of intracellular reactive oxygen species (ROS) caused by hyperglycemia, most plausibly by promoting heme oxyegenase-1 (HO-1) expression in skeletal muscle cells. Consequently, tyrosol exerts cytoprotective function against hyperglycemia-induced oxidative stress in skeletal muscle cells, increases their proliferation vigorously, and simultaneously suppresses apoptosis. Furthermore, tyrosol grossly increases the secretion of vascular endothelial growth factor-A (VEGF-A) and platelet-derived growth factor-BB (PDGF-BB) from skeletal muscle cells. This leads to enhanced proliferation and migration capabilities of vascular endothelial and smooth muscle cells, two types of cells which responsible in forming blood vessels, through cell-cell communication. Finally, in vivo experiment using the diabetic HLI mouse model showed that tyrosol injection into the gastrocnemius muscle of the ischemic hind limb significantly enhances the formation of functional blood vessels, and subsequently leads to significant recovery of blood perfusion. Overall, our findings highlight the potential of the pharmacological application of tyrosol as a small molecule drug for therapeutic angiogenesis in diabetic HLI patients.